REGUŁY OCHRONY KONKURENCJI W SEKTORZE MEDIÓW AUDIOWIZUALNYCH WE WSPÓLNOCIE EUROPEJSKIEJ - Skoczny, Tadeusz (Wydział Prawa i Administracji UAM, 2006)
The article characterises the new competition protection rules which have been recently applied to the overall audiovisual sector and focuses on actions against horizontal collusion in the sports rights. Also analysed are the most recent Community efforts to ensure the open character of online markets endangered by vertical agreements covering intellectual property rights and the ever-growing impact of merger control on the shape and function of the sector, and in particular the implications of such concentration on the media plurality. The article concludes that the Polish Competition Authority will also have to consider similar problems to those dealt with in the Community and especially the need to keep the access to premium content and proprietary infrastructure open.
THE APPLICATION OF COMPETITION RULES TO THE AUDIOVISUAL MEDIA SECTOR IN THE EUROPEAN COMMUNITY